2019
DOI: 10.1021/acs.jnatprod.8b00839
|View full text |Cite
|
Sign up to set email alerts
|

Leucinostatin Y: A Peptaibiotic Produced by the Entomoparasitic Fungus Purpureocillium lilacinum 40-H-28

Abstract: Leucinostatin Y, a new peptaibiotic, was isolated from the culture broth of the entomoparasitic fungus Purpureocillium lilacinum 40-H-28. The planar structure was elucidated by detailed analysis of its NMR and MS/MS data. The absolute configurations of the amino acids were partially determined by an advanced Marfey’s method. The biological activities of leucinostatin Y were assessed using human pancreatic cancer cells, revealing the importance of the C-terminus of leucinostatins for preferential cytotoxicity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
(59 reference statements)
1
19
0
2
Order By: Relevance
“…Momose et al showed that leucinostatin Y, having ac arboxylic acid instead of at erminal amine,w as far less active against bacteria, fungi, and cancer cells than leucinostatin A( 1a). [21] However, comprehensive structure-activity relationships (SAR) have not been reported, and pressing issues remain unanswered. Here we present the first comprehensive structure-activity relationship of leucinostatin derivatives,d etermine the structural imperatives for in vitro antiprotozoal activity,a nd optimize the selectivity of the molecules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Momose et al showed that leucinostatin Y, having ac arboxylic acid instead of at erminal amine,w as far less active against bacteria, fungi, and cancer cells than leucinostatin A( 1a). [21] However, comprehensive structure-activity relationships (SAR) have not been reported, and pressing issues remain unanswered. Here we present the first comprehensive structure-activity relationship of leucinostatin derivatives,d etermine the structural imperatives for in vitro antiprotozoal activity,a nd optimize the selectivity of the molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Replacement of the unsaturated acyl chain with acetyl resulted in a1 000-fold decrease of the affinity.I na ddition, alanine scanning revealed that only the replacement of Aib-2 was tolerated, whereas replacement of amino acids Aib-3, Leu-5 and AHMOD-8 reduced the activity by an order of magnitude.Momose et al showed that leucinostatin Y, having ac arboxylic acid instead of at erminal amine,w as far less active against bacteria, fungi, and cancer cells than leucinostatin A( 1a). [21] However, comprehensive structure-activity relationships (SAR) have not been reported, and pressing issues remain unanswered. Here we present the first comprehensive structure-activity relationship of leucinostatin derivatives,d etermine the structural imperatives for in vitro antiprotozoal activity,a nd optimize the selectivity of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The HR-ESI-MS spectrum indicated a molecular formula of C 58 H 105 N 10 O 13 corresponding to a mass of 1149.7864 [M + H] + and 12 degrees of unsaturation. As compared to leucinostatin Y [12], it lacked two carbons, one hydrogen, and two oxygens, which was confirmed by 13 C-NMR and 1 H-NMR spectroscopy. The complete assignments of all carbons are listed in Figure 1, Figure 2, and Figure S1 (available in supplementary data).…”
Section: Isolation and Structure Elucidation Of Secondary Metabolitesmentioning
confidence: 74%
“…P. lilacinum is known for the production of seven congeners of leucinostatins: A, B, C, D, F, H and K (Wang et al 2016). Recently, a new peptaibiotic called leucinostatin Y was isolated from the culture broth of P. lilacinum (Momose et al 2019). In a previous independent study, we also determined leucinostatins H and K as the major compounds in the culture filtrate of P. lilacinum based on the NMR studies (Elsherbiny et al 2019).…”
Section: Discussionmentioning
confidence: 99%